Mosquito Control Methods and Dengue Fever Disease: a Literature Review - Aulia Khairunnisa; Risti Graharti (CV. Jasa Sukses Abadi, 2026)
Dengue Hemorrhagic Fever (DHF) is one of the vector-borne diseases that remains a public health challenge in Indonesia, characterized by high incidence rates, widespread vector distribution, and an increased risk of outbreaks in various endemic areas. The transmission of the dengue virus is greatly influenced by community behavior, residential environmental conditions, and the bioecology of the Aedes aegypti mosquito, which is able to breed in clean water puddles around homes. The dengue virus consists of four serotypes and can survive through vertical and horizontal transmission mechanisms, thereby strengthening the chain of transmission in the environment. On the other hand, vector control efforts using larvicides and chemical insecticides are still widely chosen by the community, even though improper use can cause insecticide resistance. This study aims to examine various methods of dengue vector control, including physical, mechanical, biological, chemical approaches, and the EcoHealth concept. The method used was a literature review of official guidelines, research articles, and the latest scientific publications on DHF and vector control. The results of the study show that physical control methods such as 3M Plus are the most effective and safest, while biological control through larval predators and environmentally friendly bacteria can reduce the larval population without causing negative ecological impacts. Chemical control still provides rapid effects, but must be used wisely to prevent resistance. The EcoHealth approach is considered more comprehensive because it involves environmental, social, cultural, and economic aspects of the community in sustainable control. In conclusion, optimal DHF control requires an evidence-based integrated strategy with cross-sector participation and the application of ecological principles to ensure long-term success in reducing disease incidence.